Development and Interplay of Two Orthogonal Fault Systems in the NW Qaidam Basin, Northern Tibetan Plateau - Huang, Kai; Wu, Lei; Zhao, Haifeng; Zhang, Junyong; Zhang, Yongshu; Xiao, Ancheng; Chen, Yan; Chen, Hanlin (Frontiers in Earth Science, 2021)
How fold and thrust belts (FTBs) evolve over time and space in a transpressional regime remains poorly understood. Based on high-resolution 3D seismic reflection data and remote sensing images, we herein present a detailed structural analysis of the Cenozoic faults in the NW margin of the Qaidam Basin that is bounded to the north by the left-reverse Altyn Tagh fault system. Two sets of orthogonal, basement-involved faults with contrasting geometries, kinematics, and temporal development are identified. One set consists of generally E-W-striking, N-dipping, reverse faults with a component of sinistral shear. They are parallel or subparallel to the Altyn Tagh fault system, led to southward tilting of the basement, and formed a local unconformity between the middle Miocene Shangyoushashan formation and underlying strata. They developed in an out-of-sequence order, and were mostly active during 43.8–15.3 Ma but in relatively tectonic quiescence with limited weak reactivation since then. The second set is mainly composed of the NNW-striking reverse faults with dextral shear components. They are approximately perpendicular to the Altyn Tagh fault system, and intensively active since ∼15.3 Ma, much later than the initiation of the E-W-striking faults. Together with published results, we ascribe the development of these two sets of orthogonal faults as the transition from transpression to left lateral slip on the central segment of the Altyn Tagh fault system. The two fault sets interplayed with each other in two ways: 1) the older E-W-striking faults were offset by younger NNW-striking faults, and 2) the younger NNW-striking faults curved to link with the preexisting E-W-striking faults. Our findings reveal that transpressional-dominated FTBs evolve in a more complicated way than the contractional-dominated ones, and more site-based case studies are needed to reveal the underlying primary principles.